An introduction to forensic linguistics: language in evidence - Coulthard, Malcolm (Routledge, 2017)
Critical, theoretical, and methodological approaches to language in legal settings -- The language of the law -- Emergency service calls and police interviewing -- Trial discourse -- The work of the forensic linguist -- Forensic phonetics -- Authorship attribution -- On textual borrowing -- The linguist as expert witness